A systematic review on environmental DNA (eDNA) Science: An eco-friendly survey method for conservation and restoration of fragile ecosystems - Ashish Sahu; Mahender Singh; Adnan Amin; Monisa Mehboob Malik; Shariq Nazir Qadri; Adnan Abubakr; S.Surya Teja; Shabir Ahmad Dar; Ishtiyaq Ahmad (Ecological Indicators)
The conservation and restoration of fragile ecosystems and their genetic resources depends on precisely assessing species diversity and richness, understanding spatiotemporal dynamics, and stock structure analysis. Traditional monitoring methods like visual surveys, physical captures, individual counting, sibling or cryptic species identification, and immature life stages (juveniles) of animals are often intrusive, time-consuming, and provide rough estimates. Environmental DNA (eDNA) has emerged as a novel powerful tool for detecting and quantifying the presence or absence of species through genetic traces left in the environment. It is particularly suited for vulnerable habitats that are sensitive to human disturbance. Herein, we present a temporal analysis from 2008 to 2024, which indicates a consistent increase in eDNA research across fragile ecosystems and their living microbes and microorganisms. Freshwater eDNA studies contribute the highest (33.93%), followed by brackish (26.19%) and marine waters (27.38%). There is a notable focus on invasive (25.48%) and endangered species (22.36%). This systematic review provides an overview of the standard methodological considerations for eDNA science, covering stages from sample collection to advanced bioinformatics processing. It addresses various pipelines, databases, and software tools, essential for accurate data interpretation. The areas for improvement in eDNA science and future directions are also presented that can improve sensitivity, scalability, and reliability. Further, the review highlights important worldwide facilities, organizations, and laboratories leading in eDNA research, along with societies, projects, and programs promoting knowledge exchange.